4-Chloro-orthophenylenediamine alters DNA integrity and affects cell survival: inferences from a computational, biophysical/biochemical, microscopic and cell-based study. Issue 24 (26th December 2022) - Khan, Shifa; Ali, Asif; Moinuddin,; Mir, Abdul Rouf; Khan, Rizwan Hasan; Alhumaydhi, Fahad A.; Habib, Safia
Abstract: The deleterious impact of toxic constituents of hair dyes over the human health has gained immense attention in the recent past. Their oncogenicity, mutagenicity, role in protein modification, impact on cellular metabolism has been documented. There is little information on the mechanism of reactivity of hair dye components with the nucleic acids and its implications. This work, therefore, uses computational, biophysical/biochemical, microscopic and cell-based study to analyze the interaction of monocyclic aromatic amine and a hair dye component, 4-chloro-orthophenylenediamine (4-Cl-OPD) with the DNA, its impact on DNA structure and cell survival. The results suggest that 4-Cl-OPD binds with the DNA in minor groove of the duplex involving three base pairs preferentially the G-C residues, induces strand breaks and makes DNA thermally labile through loss of hydrogen bonding/base unstacking. 4-Cl-OPD causes fragmentation of DNA, reduction in size of the molecule, alters B-DNA conformation and disrupts its secondary structure. The modified DNA gives fragmented appearance, shows broken strands and aggregation in ultra-structural analysis. 4-Cl-OPD induces ROS generation in lymphocytes, increases the comet's average tail length and reduces the viability of lymphocytes. This study forms a base for establishing the direct toxicity of 4-Cl-OPD at the molecular and cellular level through direct production of superoxide radical Communicated by Ramaswamy H. Sarma